Kamisama kiss. Vol. 23 - Suzuki, Julietta; Kimura, Tomo (Viz Media, 2017)
The continuing adventures of Nanami Momozono and Tomoe and their efforts to stop Kirihito from reuniting Akura-oh's spirit with his body.